Quantitative flow measurement and visualization of cavitation initiation and cavitating flows in a converging-diverging nozzle - Ahmed, Zayed (Kansas State University, 2017)
Cavitation is the formation of vapor phase from the liquid phase by reduction in its absolute pressure below the saturation pressure. Unlike boiling, where the temperature of the liquid is increased to cause vaporization, the reduction in the pressure alone can cause the liquid to turn into vapor. Cavitation is undesirable in many engineering applications as it is associated with reduction in efficiency and is known to cause damage to pump and propeller components. However, the endothermic nature of cavitation could be utilized to create a region of low temperature that could be utilized to develop a new refrigeration cycle. The work presented in this thesis is part of ongoing research into the potential cooling capacity of cavitation phenomena, where the cavitation in a converging-diverging nozzle is being investigated. Due to the constricting nature of the throat of the converging-diverging nozzle, the liquid velocity at the throat is increased, obeying the continuity law. With an increase in velocity, a reduction in absolute pressure is accompanied at the throat of the nozzle according to the Bernoulli’s principle. The local absolute pressure at the throat can go lower than the saturation vapor pressure, thereby causing the fluid to cavitate. The effect of water temperature on the flowrates, the onset of cavitation within the nozzle, and the resulting length of the cavitation region within the nozzle are the subject of this thesis. Experimental results and analysis are presented which also show that near the onset of cavitation, the flowrate can go beyond the choked flowrate, causing the local pressure in the throat to go well below zero for an extended amount of time in the metastable state, before nucleating (cavitating) into a stable state. Flow visualization using a high speed digital camera under different operating conditions was aimed at investigating the region of cavitation onset, which appears to be associated with boundary layer separation just downstream of the nozzle throat. In order to delay the boundary layer separation point in the downstream section of the nozzle, the diffuser region of the nozzle was modified to enable two flow paths, where one path would suck the flow near the inner walls of the nozzle and the other would allow the bulk of the flow to pass through. This was achieved with the use of inserts. Various inserts were tested in an attempt to capture the effect of inserts on the cavitation phenomena. Their effect on the flowrates, length of two phase region, and cavitation onset are presented in this thesis.
Keywords: Cavitation; Two phase flow; Converging-diverging nozzle; Flow visualization